Unprecedented Chain‐Length‐Dependent Conformational Conversion Between 11/9 and 18/16 Helix in α/β‐Hybrid Peptides1. (26th September 2014) - Legrand, Baptiste; André, Christophe; Moulat, Laure; Wenger, Emmanuel; Didierjean, Claude; Aubert, Emmanuel; Averlant‐Petit, Marie Christine; Martinez, Jean; Calmes, Monique; Amblard, Muriel
Abstract α, β‐Hybrid oligomers of varying lengths with alternating proteogenic α‐amino acid and the rigid β2, 3, 3‐trisubstituted bicyclic amino acid ABOC residues were studied using both X‐ray crystal and NMR solution structures. While only an 11/9 helix was obtained in the solid state regardless of the length of the oligomers, conformational polymorphism as a chain‐length‐dependent phenomenon was observed in solution. Consistent with DFT calculations, we established that short oligomers adopted an 11/9 helix, whereas an 18/16 helix was favored for longer oligomers in solution. A rapid interconversion between the 11/9 helix and the 18/16 helix occurred for oligomers of intermediate length.